Gilteritinib - Raghunathan, Harini; Karunakaran, Parathan (Indian Journal of Medical and Paediatric Oncology, 2025)
Acute myeloid leukemia (AML) is a heterogeneous and aggressive form of blood cancer that affects the myeloid lineage of the cells. Among various genetic mutations associated with AML, the FLT-3 mutation is one of the most common and associated with poor prognosis. Gilteritinib (previously known as ASP2215) is the first tyrosine kinase inhibitor approved as monotherapy for treatment of relapsed/refractory AML.We review gilteritinib in detail, including its mechanism of action, pharmacology, efficacy, toxicity profile, and key clinical trials.
Keywords: FLT3 mutation; relapsed/refractory AML; TKI; gilteritinib